The protection of the environment through clinical legal education: the interposition of popular actions by the Public Actions Group in Colombia - Gumucio Solis, Constanza (Revista de Derecho Ambiental, 2019)
The legal system of Colombia, by the incorporation of popular actions, has allowed many actors to appeal to the courts looking to enforce diferents rights, one of those are the right to a healthy environment and the management and use of natural resources. Due to the wide legitimacy to act when these rights are affected, the Legal Clinics have appeared as a principal actor in the national courts where, through strategic litigation, they seek to achieve the protection of those rights. One of these legal clinics is the Public Actions Group of the University of Rosario, where through a rigorous selection of cases, they have achieved an effective protection of the environment, through the interposition of popular actions.